2011
DOI: 10.4028/www.scientific.net/msf.689.385
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of a Novel High-Strength Aluminum-Lithium Alloy

Abstract: As a heat treatable aluminum alloy to be used in T6 and T8 temper, belongs to Al-Cu-Li system, a novel high-strength aluminum-lithium alloy 2A97 was developed. In order to improve the relationships of strength and ductility and fracture toughness, and to urge the applications in the aeronautical and aerospace industries, the effects of normal heat treatments and thermomechanical heat treatments on the mechanical properties and fracture toughness were investigated by Transmission Electron Microscope(TEM), Scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Thus, the relations of the orientation, shape, size and distribution of the strengthening phases within the alloy matrix are vitally important. The main characteristics that affect the mechanical properties of previous generation Al-Li alloys and lead to anisotropy in the tensile properties are summarized in Table 5 [109] , [110] , [111] , [112] , [113] , [114] , [115] , [116] , [117] , [118] , [119] .…”
Section: Anisotropic Behavior Of the Al-li Alloysmentioning
confidence: 99%
“…Thus, the relations of the orientation, shape, size and distribution of the strengthening phases within the alloy matrix are vitally important. The main characteristics that affect the mechanical properties of previous generation Al-Li alloys and lead to anisotropy in the tensile properties are summarized in Table 5 [109] , [110] , [111] , [112] , [113] , [114] , [115] , [116] , [117] , [118] , [119] .…”
Section: Anisotropic Behavior Of the Al-li Alloysmentioning
confidence: 99%
“…However, this alloy has some problems such as yielding low fracture toughness and ductility in T8 temper while possessing high tensile strength, and yielding a fracture toughness and high ductility in T6 temper while having low strength. Investigations revealed that the fracture toughness and ductility were enhanced in this alloy by 4% deformation after under aging at low temperatures [41].…”
Section: Aluminum-lithium Alloysmentioning
confidence: 89%
“…Age hardening response is additional advantage of Al-Li alloys [22]. Yuan et al [41] investigated the influence of thermomechanical and normal heat treatments on the fracture toughness and mechanical properties of a new generation of aluminum-lithium alloy (2A97). They aimed to enhance the relationships of fracture toughness, ductility, and strength to make them proper candidates for applications in the aeronautical industries.…”
Section: Aluminum-lithium Alloysmentioning
confidence: 99%
“…Few of the strengthening phases were found in Al-Cu-Li alloys include δ´(Al 3 Li), T1(Al2CuLi), and θ´(Al 2 Cu). Factors such as thermo-mechanical processing, corrosion resistance, composition, microstructure, heat treatment, and manufacturing techniques impact the mechanical properties of Al-Li alloys used in the past [75][76][77][78][79][80][81][82][83][84][85].…”
Section: Tensile Properties Of 2nd Generation Alloysmentioning
confidence: 99%